2020
DOI: 10.1530/joe-19-0319
|View full text |Cite
|
Sign up to set email alerts
|

Telmisartan prevents development of obesity and normalizes hypothalamic lipid droplets

Abstract: The AT1 receptor blocker telmisartan (TEL) prevents diet-induced obesity. Hypothalamic lipid metabolism is functionally important for energy homeostasis, as a surplus of lipids induces an inflammatory response in the hypothalamus, thus promoting the development of central leptin resistance. However, it is unclear as to whether TEL treatment affects the lipid status in the hypothalamus. C57BL/6N mice were fed with chow (CONchow) or high-fat diet (CONHFD). HFD-fed mice were gavaged with TEL (8 mg/kg/day, 12 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 59 publications
4
27
1
1
Order By: Relevance
“…All articles found were published in English. At the final stage of the writing process, we conducted a new search (January 2021) and included three more articles, for a total of 24 studies [15,51,57,58,[63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82]. These steps are described in the flowchart presented in Figure 4.…”
Section: Resultsmentioning
confidence: 99%
“…All articles found were published in English. At the final stage of the writing process, we conducted a new search (January 2021) and included three more articles, for a total of 24 studies [15,51,57,58,[63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82]. These steps are described in the flowchart presented in Figure 4.…”
Section: Resultsmentioning
confidence: 99%
“…Taken together, these recent data showed that hypothalamic ceramide metabolism could be regulated by peripheral signals and can open new avenues for future treatments of obesity. This approach is supported by evidence that the antiobesity effect of telmisartan – an angiotensin II receptor type 1 antagonist – is mediated by preventing hypothalamic ceramide accumulation ( Figure 4 ) [ 60 ].
Figure 4 Pathophysiological regulation of hypothalamic de novo ceramide synthesis: impact on body weight gain.
…”
Section: Does De Novo Ceramide Biosynthesis Play a Role In Hypothalamic Lipotoxicity-induced Obesity?mentioning
confidence: 91%
“…Neuroinflammation has been associated with a variety of further diseases including amyotrophic lateral sclerosis (ALS), epilepsy, traumatic brain injury, Parkinson’s disease, and Huntington’s chorea ( 149 ) but also with non-neurological chronic conditions such as rheumatoid arthritis, obesity and diabetes ( 150 , 151 ). While the contribution of platelets to central nervous system (CNS)-inflammation in some of these diseases has recently been reviewed elsewhere ( 152 ), this review focuses on MS and Alzheimer’s disease (AD).…”
Section: Contribution Of Platelets To Neurovascular Inflammation In Nmentioning
confidence: 99%